Investigating the Feasibility of Brief Compassion Focused Therapy in Individuals in Treatment for Opioid Use Disorder - Molly Carlyle; Helen Rockliff; Rachel Edwards; Crina Ene; Anke Karl; Beth Marsh; Lucie Hartley; Celia JA Morgan (SAGE Publishing, 2019)
Opioid use disorder (OUD) is reaching epidemic proportions worldwide, and is notoriously difficult to treat. Compassion focused therapy (CFT) has emerged as therapeutic tool for treating individuals exhibiting high levels of self-criticism and low self-esteem, both of which are common in OUD. Until now, however, there had been no research investigating this therapy in patients with OUD. Before running a premature clinical trial, it is important to fully assess the feasibility and acceptability of this treatment in this group of individuals. We aimed to assess the feasibility of CFT treatment in individuals with OUD in a short group intervention, which was co-created by the research team, service users and a local drugs service. The intervention involved three 2-hour sessions held over 3 weeks, where participants engaged in compassion-orientated psychoeducation and self-compassionate exercises. Individuals were randomly assigned to either the CFT group (n = 15), the active control (relaxation) group (n = 12) or the waitlist control group (n = 11). Of 103 individuals approached, 45% attended a baseline visit suggesting the treatment was acceptable to this group. A relatively low attrition rate across the 3 groups was found for CFT (21.1%), with no difference in drop-out between the groups. Qualitative analysis of interviews with participants identified a desire for more sessions. Compassion focused therapy was thus feasible and well-tolerated in those with OUD, and a further trial to evaluate any clinical differences may be warranted.